Enterprise 2.0 - Keyes, Jessica (Auerbach Publications, 2016)
Enterprise 2.0 (E 2.0) has caught the collective imagination of executives who are innovating to radically change the face of business. E 2.0 takes full benefit of social networking, including blogs, discussion boards, mashups, and all that is sharable and combinable. Examining organizations and their social activities, Enterprise 2.0: Social N.